HIPERGLUCEMIA COMO FACTOR DE RIESGO EN PACIENTES CON ENFERMEDAD CEREBROVASCULAR AGUDA. - Araujo, Luz; Velásquez, Mery Guerra; Reyna-Villasmil, Eduardo; Mejia-Montilla, Jorly; Bolívar, Joel Santos; Reyna-Villasmil, Nadia (MedULA)
The objective of research was to identify hyperglycemia as a risk factor in patients with diagnosis of acute cerebrovascular disease. An explicative, prospective and transversal research was done with an intentional non-probabilistic sample of 47 patients (group A) with diagnosis of acute cerebrovascular disease that assisted to Hospital Central "Dr. Urquinaona". There were also selected patients who assisted to emergency with different pathologies of acute cerebrovascular disease (group B). Presence of hyperglycemia, risk factors and relative risk were evaluated. Mean age of cases was 71.5 ± 15.2 years-old and in controls was 65.9 ± 15.3 years-old (p = ns). Patients in group A presented a higher frequency of hypertension and hyperglycemia than patients in group B (p < 0.05). The rest of risk factors did not show significant differences between case and controls (p = ns). Relative risk classification showed that hypertension (RR = 1.85; CI 95%, 1.18 - 2.91) and hyperglycemia (RR = 1.75, CI 95%, 1.19 - 2.59) were significant for acute cerebrovascular disease. None of the other factor showed a significant risk value (p = ns). It is concluded that hyperglycemia is a risk factor in patients with diagnosis of acute cerebrovascular disease.